USULAN RUMUSAN HUKUM ACARA (IUS CONSTITUENDUM) PENGUJIAN PERATURAN PERUNDANG-UNDANGAN DI BAWAH UNDANG-UNDANG OLEH MAHKAMAH AGUNG - Effendi, Maftuh; Cahya Indra Permana, Tri (Jurnal Media Hukum, 2018)
The implementation of juridical control of the legislation under the law by the Supreme Court through judicial review until nowadays was not running optimally. One of the causes of the less optimal quality of the decision to test regulations under the law was the absence of procedural law for the testing of material test rights that can accommodate the needs of the proceedings. These article wishes to propose a number of ideas so that in the future the MA will begin to discuss the procedural law for the testing of laws and regulations under the Act through trials that were open to the public. This is based on the principle that disputes in the laws and regulations under the Act not only examine juridical aspects, but also facts, and the decisions are final and binding, so that they have a broad impact on the public. Therefore, it is necessary to develop material on the contents of the procedural law for the testing of laws and regulations under a law that reflects the principle of fairness in order to increase public trust.